The effects of trust and distrust on ICT-enabled information sharing in supply chains: Evidence from small- and medium-sized enterprises in two developing economies. Issue 3 (12th August 2019) - Mirkovski, Kristijan; Davison, Robert M.; Martinsons, Maris G.
Abstract : Purpose: Drawing on transaction cost economics (TCE) and social exchange theory (SET), the purpose of this paper is to explain why and how external environment, governance structures and interpersonal relationships influence information and communication technology (ICT)-enabled information sharing in supply chains (SCs) of small- and medium-sized enterprises (SMEs) from developing economies. Design/methodology/approach: The authors adopt a theory-building approach using a multiple case study design, including four SMEs operating in SCs from two developing economies (i.e. Republic of North Macedonia and People's Republic of China), in which the authors conduct both within-case and cross-case analyses. Findings: Social bonds (known as vrski in Macedonian and guanxi in Chinese) were found to govern buyer–supplier exchanges by supporting the establishment of personal trust and the reduction of distrust. These social bonds compensate for the institutional deficiencies in developing economies and thus encourage ICT-enabled information sharing by SMEs in their SCs. Research limitations/implications: By applying the theoretical perspectives of TCE and SET to the cross-case analysis, the authors develop nine propositions to explain ICT-enabled information sharing and its interdependencies with external environment, governance structures and interpersonal relationships in developing economies. Further research is recommended to refine and test the generalizability of the theoretical model. Practical implications: Firms have to develop and nurture social bonds with their suppliers from developing economies to reduce risks related to the environmental uncertainty and institutional voids. This can increase trust and decrease distrust associated with ICT-enabled information sharing. Originality/value: The study examines why and how external environment (environmental uncertainty and institutional environment), social bonds (vrski and guanxi) and interpersonal mechanisms (trust and distrust) influence ICT-enabled information sharing of SMEs operating in developing economies.